PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATERI TRIGONOMETRI - Mohammad Jufri (SIGMA, 2021)
This study aims to determine the increase in students' understanding of trigonometry material for class XI-MIPA 2 SMA Negeri 1 Pademawu in the 2019/2020 academic year through the application of a problem based learning model. This research is a classroom action research and is carried out in two cycles with several stages, namely: planning, implementation, observation, and reflection. Researchers used the method of observation, questionnaires, tests, and interviews. Student activity increased by 0.06, namely in the first cycle an average of 3.55 was obtained in the very good category and the second cycle obtained an average of 3.61 in the very good category. Student responses were categorized as positive with an increase of 3%, namely in the first cycle the percentage was 90% and in the second cycle the percentage was 93%. The test results also increased by 16.67%, namely in the first cycle the percentage was 70% and in the second cycle the percentage was 86.67%. The improvement of test results in cycle II is said to be classically complete because the percentage obtained is 85 %. So it can be said that the application of the problem based learning model can improve students' understanding of trigonometry material